2013
DOI: 10.2174/1566524011313040010
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia, Hypoglycemia and Dementia: Role of Mitochondria and Uncoupling Proteins

Abstract: Diabetes mellitus is one of the most prevalent chronic diseases. Since glucose is the main fuel of the brain, its levels should be maintained within a narrow range to ensure normal brain function. Indeed, the literature shows that uncontrolled blood glucose levels, whether too high or too low, impact brain structure and function potentiating cognitive impairment. Uncoupling proteins (UCPs) are a family of mitochondrial anion carrier proteins located on the inner mitochondrial membrane, and their primary functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 187 publications
1
13
0
Order By: Relevance
“…The results of this study are concomitant with the results of the study carried out by the [2] which showed that hypoglycemia may cause an increase in oxidative stress in the brain tissue, and also with the study carried out by [8] which stated that hypoglycemia has led to an increase in the level of MDA with the decreased activity of SOD and GSH content of the brain's cortex and is also consistent with studies conducted by [32], [33], [34] and [35]. The accumulation of large quantities of zinc in neurons as a well as the result of decreased glucose level; has led to an increase in the production of ROS in the nerve cells which led to increased oxidative stress in the brain cortex and the hypothalamus and hypoglycemic coma and brain injury are complications.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study are concomitant with the results of the study carried out by the [2] which showed that hypoglycemia may cause an increase in oxidative stress in the brain tissue, and also with the study carried out by [8] which stated that hypoglycemia has led to an increase in the level of MDA with the decreased activity of SOD and GSH content of the brain's cortex and is also consistent with studies conducted by [32], [33], [34] and [35]. The accumulation of large quantities of zinc in neurons as a well as the result of decreased glucose level; has led to an increase in the production of ROS in the nerve cells which led to increased oxidative stress in the brain cortex and the hypothalamus and hypoglycemic coma and brain injury are complications.…”
Section: Discussionsupporting
confidence: 90%
“…In neurons, high glucose concentration induces depolarization of the mitochondrial membrane (Liu et al, 2006;Russell et al, 2002), an abnormal mitochondrial activity, as well as impaired bioenergetics status (Fernyhough et al, 2010;Reddy, 2009). As a whole, the aforementioned evidences show the relevance of mitochondria for the evolution of neurodegenerative disorders and aging (Cardoso et al, 2013), however, these events can be inhibited using antioxidants specific for mitochondria (Cao et al, 2012;Moreira et al, 2007).…”
Section: Diabetes and Damage To Mitochondriamentioning
confidence: 99%
“…Therefore, it is likely that these pairs share the same aging-related genes. Moreover, brain-related diseases, such as Neurogenerative disease and Dementia, are closer to the four diseases on the far right-hand side: Hypertension [ 39 , 40 ], Cardiovascular disease [ 41 43 ], Diabetes mellitus [ 44 46 ], Hyperglycemia [ 47 , 48 ]. This is a demonstration of how our approach can provide overviews of scientific literature to date, and reaffirm scientific results that are understood in the science world.…”
Section: Resultsmentioning
confidence: 99%